2022
DOI: 10.1021/acs.iecr.1c04625
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Graphene Aerogel Microspheres Used as Electrocatalyst Supports for Methanol Oxidation

Abstract: Nitrogen-doped graphene aerogel microspheres (rGNAMs) are prepared by electrospraying the graphene oxide dispersion with pyrrole and an oxidation agent and then subjecting it to freeze-drying and thermal annealing. The rGNAMs possess a high surface area, an interconnected pore structure, and uniform N doping. The Pt nanoparticles (Pt NPs) are loaded into rGNAMs through a hydrothermal reduction reaction to obtain the Pt/rGNAM composite catalyst for methanol electrooxidation. The N-doping structure of rGNAMs can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Typically, for Pt@In 2 O 3 , the peaks with binding energies of 70.23 and 73.48 eV are attributed to Pt 4f 7/2 and Pt 4f 5/2 of Pt 0 , while those at 70.73 and 73.88 eV are assigned to Pt 4f 7/2 and Pt 4f 5/2 of Pt 2+ , respectively. 33–36 Comparatively, both metallic Pt and Pt 2+ species are also detected in Pt/In 2 O 3 , but the binding energies of the characteristic peaks of Pt species in Pt@In 2 O 3 are smaller than those in Pt/In 2 O 3 . This finding can be understood as the Pt species replacing the In 3+ ions in the In 2 O 3 lattice or locating at the defective sites.…”
Section: Resultsmentioning
confidence: 93%
“…Typically, for Pt@In 2 O 3 , the peaks with binding energies of 70.23 and 73.48 eV are attributed to Pt 4f 7/2 and Pt 4f 5/2 of Pt 0 , while those at 70.73 and 73.88 eV are assigned to Pt 4f 7/2 and Pt 4f 5/2 of Pt 2+ , respectively. 33–36 Comparatively, both metallic Pt and Pt 2+ species are also detected in Pt/In 2 O 3 , but the binding energies of the characteristic peaks of Pt species in Pt@In 2 O 3 are smaller than those in Pt/In 2 O 3 . This finding can be understood as the Pt species replacing the In 3+ ions in the In 2 O 3 lattice or locating at the defective sites.…”
Section: Resultsmentioning
confidence: 93%
“…In a study, the ECSA of the Pt nanoparticles on N‐doped graphene support is approximately 78% higher than that of the Pt nanoparticles on graphene support, which is attributed to the superior dispersion of the Pt nanoparticles on N‐doped support 42 . In another study, NGA microspheres with different N doping amounts supported catalysts for MOR showed higher ECSA due to the better loading and anchoring of Pt, but lower ECSA is observed due to the obvious agglomerations 43 …”
Section: Resultsmentioning
confidence: 95%
“…Mesoporous carbons are attractive as catalyst supports because of their large surface area, high conductivity, controlled mesoporous structure, and excellent stability in both acid and basic solutions. [29,30] Furthermore, N-doping of mesoporous carbons can increase Pt dispersion by enabling strong Pt-N interactions between the N-functionalities of N-doped carbons and either Pt precursors [31] or Pt NPs, [32][33][34] (or Pt clusters and single sites) where the strong Pt-N interactions can also stabilize Pt and inhibit Pt entity detachment. [31] In this work, we synthesized highly dispersed Pt entities supported on mesoporous N-doped carbon (MPNC) nanospheres for improved HER.…”
Section: Introductionmentioning
confidence: 99%